Structural, flow mechanism and thermal roperties study of oil palm (Elaeis guineensis) trunk syrup. - Ariffin, Fazilah (Universiti Sains Malaysia, 2016)

(untitled)
Oil palm plantation has taken up to 20% of agricultural land in Malaysia. During replantation, the oil palm tree is cut down and this is producing a large amount of biomass waste. The saps from the trunk were studied to have a high content of sugar that is increasing as the trunk stored until 60 days.